Keto-enol tautomerism in the development of new drugs - Araujo de Oliveira, Ana Paula; Wegermann, Camila Anchau; Ferreira, Ana Maria Da Costa (Frontiers in Chemical Biology, 2024)
In the development of new medicinal or pharmaceutical agents, the presence of isomers is a huge challenge, since the main goal is to obtain the most active compound in high purity and yield. Tautomerism is a phenomenon quite common in biomolecules, that also appears in many drugs, and strategies to control the corresponding desired species and related equilibria conditions leading to an efficient chemical speciation are frequently required. In the literature, there are many reports about the presence of tautomers, despite some papers which do not emphasize properly their occurrence or its importance for the differences verified in biological activity. Herein, a discussion about tautomers, observed both in metalated and non-metalated compounds, and their importance in the biological properties of promising drugs is revisited. Mainly, keto-enol equilibria among imines and hydrazones oxindole derivatives are showcased, based on significant examples, as well as strategies to improve their speciation or to better elucidate their modes of action.